Development of an acceptable canned "Tawilis" (Harengula tawilis) in oil - Ong, Emily Chua
A preliminary production of canned "tawilis" in oil was done based on the formulation developed by Mr. Francisco Lopez. Test results showed that the low-acid product is microbiologically safe, and sensorially acceptable. However, certain necessary measures were undertaken primarily to improve its sensory qualities, particularly texture. These measures involve modification of product formulation, determination of optimum brining and drying time combination as pretreatment, and establishment of adequate process schedule. Results of the tests conducted revealed that a brining and drying time combination of 60 and 40 minutes, respectively, improves significantly the sensory qualities of the product. On the other hand, a process schedule of 45 minutes at 253°F based in Bacillus stearothermophilus was found to be adequate to achieve commercial sterility. Cost computation showed that each can cost P22.12.